The Potential Development Of Balinese Beef Business In Rato Village Lambu District Bima Regency - Harmayani, Ria; Alimuddin, Alimuddin; Gunadi, Sahrul; Permadi, Hari; Afrizal, Afrizal (Fakultas Pertanian Universitas Muara Bungo, 2023)
This research was conducted in Rato village Lambu District Bima Regency on July-October 2022. The purpose of this research is to know the potential development of beef cattle in Rato Village Lambu district Bima regency. This research used study case method with reference toward restriction that study case is collecting data by taking some elements then those elements were analyzed and conclusion that was drawn only valid for those elements which have been investigated before. Data were analyzed using two ways, descriptive analysis and Economic Analysis. Descriptive analysis was used to know the state of beef cattle business and economic analysis was used to know the composition of production cost, income, profit of beef cattle and R/C ration. The development of beef cattle in Rato Village, Lambu District has the potential to be carried out as shown in the value of the return cost ratio (R/C) ratio and its business feasibility. The value of R/C 1 in the balinese cattle business is based on the number of livestock owned in Rato Village, Lambu District, Bima Regency. Small scale beef cattle business (1-5 heads) has an R/C ratio of 3.02, medium scale (6-10 heads) obtains an R/C ratio of 3.19 which illustrates that both small and medium scale beef cattle businesses get profit because the value of R/C Ratio 1 so that the farm is profitable.